Mechanical properties of radish petioles and calibration of cohesion parameters in discrete element models - Zhang, Zhendong; Bao, Guocheng; Yuan, Yanwei; Lv, Zhouyi; Chen, Xinxin; Chen, Xuedong; Yang, Wei (Frontiers in Plant Science, 2025)
An understanding of the biomechanical properties of radish petioles is critical for the rational design of harvesting machinery and the optimization of the harvesting process. At present, research on the biomechanical properties of radish petioles is relatively scarce, and there is a lack of bonding parameters for the discrete element simulation model of radish petioles. To address these challenges, this study explores the impact of varying petiole parts, moisture content, and tissue structure on their mechanical properties through histological analysis and torsional testing. Subsequently, a discrete element simulation model for radish petioles, suitable for mechanized harvesting processes, was developed based on the BondingV2 model. The model’s bonding parameters were optimized through Plackett-Burman and central composite experiments. The experimental results indicate that the torsional modulus of the radish petiole is significantly influenced by moisture content and tissue structure, with the highest torsional modulus observed at the petiole’s distal end, exhibiting optimal mechanical performance at intermediate moisture levels. The petiole’s distal end exhibited the following properties: unit area normal stiffness coefficient is 2×109 N/m², unit area shear stiffness coefficient (3.12×109 N/m²), normal strength (1.5×10¹¹ Pa), shear strength (7.5×10¹0 Pa), and Bonded Disk Scale (1.17). The simulation results of axial tension, torsional bending, three-point bending, and field tests exhibited errors of 4.46%, 8.8%, 0.41%, and 2.1%, respectively, when compared to the corresponding physical test results, thereby validating the reliability of the bonding parameters calibrated for the distal petiole of radish at the optimal moisture content. The findings of this study provide a theoretical foundation and technical support for the optimization of mechanized harvesting equipment for radishes.